Relationship of social sustainability, operational performance and economic performance in sustainable supply chain management - Ngoc Hong Duong (Global Business & Finance Review (GBFR), 2022)
Purpose: Over the past two decades, sustainable development and green economy approaches have been implemented in different fields, including supply chain management. In developed countries, sustainable supply chain management (SSCM) has attracted attention from both academia and industry. However, there is a substantial knowledge gap about supply chain social sustainability in developing countries. Hence, the main purpose of this study is to present the link between social sustainability and economic performance with the mediating role of operational performance in sustainable supply chain management. Design/methodology/approach: The PLS-SEM model is applied to identify factors affecting social sustainability and the relationship between social sustainability, operational performance, and economic performance in Vietnam. Findings: The study broadens the concept and emphasizes the importance of sustainable development in the context of Vietnam and provides recommendations for managers on strategic planning and developing business towards sustainability. This study also encourages managers to enrich employees' welfare and working conditions and con- tribute to the local community. Research limitations/implications: The social indicators in developing countries are distinct from those in developed countries. Hence, this study may only apply in the context of developing countries. There are three main pillars of sustainable development, including economic (profit), environment (planet), and society (people). In this research, the author only examines the social and economic aspects. Originality/value: The outcomes of this study demonstrate a clear link between the social and economic elements of sustainability. While demonstrating how fully implemented Social sustainability improves economic performance, this study stimulates academic research about the interrelationship of sustainability elements in supply chains.
Keywords: 650; Social sustainability; Operational performance; Economic performance; Sustainable development